PERSEPSI GURU TERHADAP ANAK YANG MENGALAMI GANGGUAN PERILAKU DALAM KEGIATAN SEKOLAH - Yuda Pramita Amelia (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background of differences in perception or perspective teachers of children who have behavioral disorders in the learning process at Junior High School 24 in Padang. The purpose of this study was to obtain an overview of teachers' perceptions of children who have behavioral disorders behavioral disorder include the presence of children in school, social interaction with the teacher's behavior, social interaction with peers and learning achievement of children behavioral disorders. The methodology of this research is descriptive quantitative approach. From the results of this study indicated that most of the teachers noticed the presence, interaction and interpretation of behavior in children at Junior High School 24 in Padang.